A systematic review of genotypes and serogroups of African swine fever virus - Qu, Hailong; Ge, Shengqiang; Zhang, Yongqiang; Wu, Xiaodong; Wang, Zhiliang (Virus genes, 2022)
African swine fever virus (ASFV) is the causative agent of African swine fever (ASF). The virus causes an acute highly hemorrhagic disease in domestic pigs, with high mortality. Although the overall genome mutation rate of ASFV, a large DNA virus, is relatively low, ASFV exhibits genetic and antigenic diversity. ASFV can be classified into 24 genotypes on the basis of the B646L gene. Cross-protected ASFV strains can be divided into eight serogroups on the basis of antibody-mediated hemadsorption inhibition. Here, we review research progress on ASFV genotyping and serogrouping, and explain how this information assists in the rapid identification of virus origin during ASF outbreaks and will aid in the development of ASF vaccines.